Implementasi Pemberian Visa Dan Izin Tinggal Dalam Masa Adaptasi Kebiasaan Baru Di Kantor Imigrasi Kelas I TPI Manado - Oroh, Andrew Johannes; Pati, Agustinus B.; Areros, William (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the implementation of granting visas and residence permits in the adaptation period of new habits at the Manado Class I TPI Immigration Office. This research was conducted from August 2022 to March 2023. The selection of information was done intentionally and purposefully. The data used were primary data and secondary data. Primary data was collected through interviews, interview guidelines to the Class I TPI Manado immigration office as the implementer of the policy of granting visas and residence permits during the adaptation period of new habits and also to foreign nationals who get these services. Secondary data was obtained from relevant agencies, namely through the Manado Class I TPI Immigration Office, Sam Ratulangi International Airport and the local government of North Sulawesi Province. Secondary data was also obtained through books obtained from local bookstores and the internet through google scholar in the form of books, journal articles, and theses/theses related to the topic of this research, namely the implementation of granting residence permits and visas during the adaptation period of new habits. The results showed that the implementation of the policy of granting visas and residence permits during the adaptation period of new habits by the Manado class I TPI immigration office was running well at that time with the support of the local government and the central government, despite experiencing several changes in rules due to situations and conditions, but the policy could be carried out well.